2020
DOI: 10.3390/ijerph17072226
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Medially Posted Insoles on Lower Limb Joint Contact Forces in Adult Acquired Flatfoot: A Pilot Study

Abstract: Flatfoot is linked to secondary lower limb joint problems, such as patellofemoral pain. This study aimed to investigate the influence of medial posting insoles on the joint mechanics of the lower extremity in adults with flatfoot. Gait analysis was performed on fifteen young adults with flatfoot under two conditions: walking with shoes and foot orthoses (WSFO), and walking with shoes (WS) in random order. The data collected by a vicon system were used to drive the musculoskeletal model to estimate the hip, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 53 publications
(84 reference statements)
4
59
0
Order By: Relevance
“…Our study found that the manifestation of the first metatarsal medial deviation induced by deforming load may be hindered by the forefoot abduction or pronation that formed a viscous cycle to provoke more deforming load. Controlling the pronation or eversion by supporting the medial longitudinal arch by orthosis (Glasoe et al, 2010;Nakagawa et al, 2019;Peng et al, 2020) may slow down the deterioration process and supplement surgical outcomes to reduce recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the manifestation of the first metatarsal medial deviation induced by deforming load may be hindered by the forefoot abduction or pronation that formed a viscous cycle to provoke more deforming load. Controlling the pronation or eversion by supporting the medial longitudinal arch by orthosis (Glasoe et al, 2010;Nakagawa et al, 2019;Peng et al, 2020) may slow down the deterioration process and supplement surgical outcomes to reduce recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al [ 46 ] measured three different conditions: using an orthotic insole, a flat foot insole and 3-D printed insole. Two studies [ 43 , 44 ], used imaging as well as pressure plates. In Murley et al [ 42 ], imaging and electromyogram were conducted at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast Park et al [ 43 ] investigated the change in pelvic angle using foot orthoses and reported a significant decrease after wearing the orthotic. Peng et al [ 44 ] investigated the patellofemoral joint and the medial and lateral tibiofemoral joint. After wearing the foot orthoses, the second peak patellofemoral contact force and the peak contact force of the ankle were significantly lower.…”
Section: Resultsmentioning
confidence: 99%
“…Controlling the patients' physical conditions, such as the joint alignment and weight-bearing state during casting, plays a vital role, aside from the geometrical fitness and maintaining the subtalar joint neutral being a rule of thumb [49]. To evaluate whether the orthosis could adjust the muscular action and internal load transfer, some studies measured the surface electromyography [50] while computer simulations were also utilized to predict the muscle force, internal joint loading, and the stress of the plantar fascia and ligaments [51][52][53].…”
Section: Discussionmentioning
confidence: 99%